EFISIENSI ALOKATIF FAKTOR PRODUKSI USAHATANI JAGUNG HIBRIDA PADA KELOMPOK MANYI MERTA TANI DESA TANGGUNTITI TABANAN - Victoria Kurniati; I Made Budiasa; Ni Putu Sukanteri; Farida Hanum (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
The objectives of this study are: 1) To analyze the production factors on the amount of hybrid corn production in Tangguntiti Village 2) To analyze the level of allocative efficiency of production factors in hybrid corn farming activities in Tangguntiti Village, the location of the study was done (deliberately), the sample in the study These 35 people were determined by the simple random sampling method with the help of the Slovin formula. This study used the Coob Douglas production function analysis method. The results of this study only variable land area, hybrid corn seeds, urea fertilizer, NPK fertilizer, pesticides, organic fertilizers, and labor together have an effect of 0.689% while 31.1% is influenced by variables outside the model with the hybrid corn production function Y = 1.046,28(X10,061)(X20,054)(X30,14)(X40,116)(X50,197)(X6-0,70)(X70,014). Production factors that have a signify-cant effect on corn production are organic fertilizers with a production elasticity of 0.197, and those that do not significantly affect hybrid corn production are land area, hybrid corn seeds, Urea fertilizer, NPK fertilizer, Pesticides, and labor with production elasticity of 0.061, 0.054, 0.140, 0.116, 0.70 and 0.014. While the inefficient: Land area, Organic Fertilizer, Pesticides, and Labor, while the inefficient production factors: Hybrid corn seeds, Urea fertilizer, and NPK fertilizer.